Carbon-Doped GaN on SiC Materials for Low-Memory-Effect Devices. (23rd August 2016) - Chen, Jr-Tai; Janzén, Erik; Rorsman, Niklas; Thorsell, Mattias; Andersson, Mats; Kordina, Olof
Abstract : AlGaN/GaN on SiC HEMT structures suitable for high power, high frequency applications are demonstrated. The material manifests record breaking thermal management and electron mobility. Moreover, thanks to the fact that the buffer layer is doped with carbon, the memory effect of processed devices is very low making system design and manufacturing significantly easier and less expensive.